Investors Facing Risk II: Loss Aversion and Wealth Allocation When Utility Is Derived From Consumption and Narrowly Framed Financial Investments - Erick W. Rengifo; Emanuela Trifan (Technische Universität Darmstadt, Department of Law and Economics, 2007)
This paper studies the attitude of non-professional investors towards financial losses and their decisions concerning wealth allocation among consumption, risky, and risk-free financial assets. We employ a two-dimensional utility setting in which both consumption and financial wealth fluctuations generate utility. The perception of financial wealth is modelled in an extended prospect-theory framework that accounts for both the distinction between gains and losses with respect to a subjective reference point and the impact of past performance on the current perception of the risky portfolio value. The decision problem is addressed in two distinct equilibrium settings in the aggregate market with a representative investor, namely with expected and non-expected utility. Empirical estimations performed on the basis of real market data and for various parameter configurations show that both settings similarly describe the attitude towards financial losses. Yet, the recommendations regarding wealth allocation are different. Maximizing expected utility results on average in low total-wealth percentages dedicated to consumption, but supports myopic loss aversion. Non-expected utility yields more reasonable assignments to consumption but also a high preference for risky assets. In this latter setting, myopic loss aversion holds solely when financial wealth fluctuations are viewed as the main utility source and in very soft form.
Keywords: C32; C35; G10; 330; prospect theory; Value-at-Risk; loss aversion; expected utility; non-expected utility; Anlageverhalten; Risikoaversion; Prospect Theory; Portfolio-Management; Value at Risk; Theorie; USA